Disruption of Epithelial Barrier of Caco-2 Cell Monolayers by Excretory Secretory Products of Trichinella spiralis Might Be Related to Serine Protease - Li, Chengyao; Bai, Xue; Liu, Xiaolei; Zhang, Yuanyuan; Liu, Lei; Zhang, Lixiao; Xu, Fengyan; Yang, Yong; Liu, Mingyuan (Frontiers in Microbiology, 2021)
The physical barrier is composed of epithelial cells which are joined together through intercellular connections. It serves to prevent pathogenic microorganisms from departing the intestinal lumen to invade host. The excretory secretory (ES) products of Trichinella spiralis are critical for invasion. However, whether ES products of T. spiralis can act on the intestinal barrier is still unknown. In this study, the role of ES products of T. spiralis muscle larvae (Ts-ML-ES) in host invasion was studied by establishing an in vitro cell monolayers model. Barrier integrity analysis by a transmembrane resistance test and a paracellular permeability assay revealed that the Ts-ML-ES was able to destroy barrier function. It occurred via a reduction in the expression of tight junction proteins, which was induced by serine proteases. Furthermore, Western bolt analysis indicated that Ts-ML-ES reduced the expression of tight junction proteins via the MAPK signaling pathway. Based on these data, we conclude that serine protease are likely the main factors from Ts-ML-ES that affect host intestinal barrier integrity by reducing the expression of tight junctions via the P38-MAPK signaling pathway. Ts-ML-ES might be a key invasion factor in T. spiralis.